Research Progress in Membrane Lipid Metabolism and Molecular Mechanism in Peanut Cold Tolerance - Zhang, He; Dong, Jiale; Zhao, Xinhua; Zhang, Yumei; Ren, Jingyao; Xing, Liting; Jiang, Chunji; Wang, Xiaoguang; Wang, Jing; Zhao, Shuli; Yu, Haiqiu (Frontiers in Plant Science, 2019)
Early sowing has been extensively used in high-latitude areas to avoid drought stress during sowing; however, cold damage has become the key limiting factor of early sowing. To relieve cold stress, plants develop a series of physiological and biochemical changes and sophisticated molecular regulatory mechanisms. The plasma membrane is the barrier that protects cells from injury as well as the primary place for sensing cold signals. Chilling resistance is closely related to the composition, structure, and metabolic process of membrane lipids. This review focuses on membrane lipid metabolism and its molecular mechanism, as well as lipid signal transduction in peanut (Arachis hypogaea L.) under cold stress to build a foundation for explicating lipid metabolism regulation patterns and physiological and molecular response mechanisms during cold stress and to promote the genetic improvement of peanut cold tolerance.